Dairy cow nutrition in organic farming systems. Comparison with the conventional system. (2nd October 2018) - Orjales, I.; Lopez-Alonso, M.; Miranda, M.; Alaiz-Moretón, H.; Resch, C.; López, S.
Abstract : The energy supplied by the high-forage diets used in organic farming may be insufficient to meet the requirements of dairy cattle. However, few studies have considered this problem. The present study aimed to analyze the composition of the diets and the nutritional status (focusing on the energy–protein balance of the diets) of dairy cattle reared on organic farms in northern Spain, which are similar to other organic farming systems in temperate regions. Exhaustive information about diets was obtained from organic (ORG) and representative conventional grazing (GRZ) and conventional no-grazing (CNG) farms. Samples of feed from the respective farms were analyzed to determine the composition. Overall, the diets used on the ORG farms were very different from those used on the CNG farms, although the difference was not as evident for GRZ. The CNG farms were characterized by a higher total dry matter intake with a high proportion of concentrate feed, maize silage and forage silage. By contrast, on ORG and GRZ farms, the forage, pasture and fibre intake were the most important variables. The ration used on ORG farms contained a significantly higher percentage of ADF and lower organic matter (OM) content than the rations used in both of the conventional farming systems, indicating that the diets in the former were less digestible. Although the protein concentration in the diets used on the grazing farms (ORG and GRZ) was higher than those used on CNG farms, the protein intake was similar. The results indicated an imbalance between energy and protein due to the low level of energy provided by the ORG diets, suggesting that more microbial protein could be synthesized from the available rumen-degraded dietary nitrogen if rumen-fermentable OM was not limiting. The imbalance between energy and protein led to a reduced amount of total digestible protein reaching the intestine and a lower milk yield per kilogram of CP intake on the ORG farms. In order to improve the protein use efficiency and consequently to reduce the loss of nitrogen to the environment, organic farming should aim to increase the energy content of cattle diets by improving forage quality and formulating rations with more balanced combinations of forage and grain.